Transformational Leadership and School Improvement Practices in Rural Secondary Education: The case of Potia National High School - Bumulyad, Michael (Azal Arts and Humanities, 2026)
School leadership plays a crucial role in fostering educational quality, organizational effectiveness, and institutional development, particularly in geographically isolated and disadvantaged schools. This qualitative case study explored the transformational leadership practices and school improvement initiatives implemented by the school head of Potia National High School in Alfonso Lista, Ifugao. The study investigated leadership approaches, administrative strategies, teacher engagement mechanisms, and challenges encountered in managing a rural secondary school. Data were collected through semi-structured interviews, document analysis, and school-based observations involving school personnel and stakeholders. Findings revealed that transformational leadership practices were manifested through collaborative decision-making, teacher empowerment, community engagement, instructional supervision, and adaptive management strategies. The study further identified that the school head’s leadership significantly contributed to teacher motivation, organizational cooperation, and school improvement initiatives despite contextual challenges such as limited resources, infrastructure constraints, and rural educational conditions. The findings underscore the importance of context-responsive and people-centered leadership practices in promoting sustainable educational development in rural secondary schools. The study contributes to the growing body of literature on educational leadership in geographically isolated Philippine educational contexts.